Occupational Safety and Health Standard of Office at PT. Bank XYZ Tower Building Medan - EL- Matury, Herlina Jamaluddin (Jurnal Penelitian Kesmasy, 2024)
The office work environment is deemed as 'safe and healthy'. Less effort is taken to manage the health hazards that lie hidden therein proactively. moreover, the effects of these hazards take time to manifest and, in many cases, irreversible damage to workers' health has already been done. Methods: A quantitative study, descriptive and observational approach was conducted under the research objective to assess the Occupational Safety and Health (OSH) Standard of Office at PT. Bank XTZ Tower Building in Medan City, from February to July 2022. The self-assessment form checklist is based on the Regulation of the Minister of Health of the Republic of Indonesia Number 48 of 2016 concerning Work Health and Safety Standards in the Office. Results: The findings show that the implementation of office safety and health standards at PT. Bank XYZ is 71% (Good). Conclusion: The OSH standard of the office has been implemented, there are aspects of the OSH Policy, implementation of Occupational Safety and Health Aspects, Ergonomic Aspects, and Work Environment Aspects.